2018
DOI: 10.1111/hypa.12401
|View full text |Cite
|
Sign up to set email alerts
|

Precarity is a Feminist Issue: Gender and Contingent Labor in the Academy

Abstract: Feminist philosophers have challenged a wide range of gender injustices in professional philosophy. However, the problem of precarity, that is, the increasing numbers of contingent faculty who cannot find permanent employment, has received scarcely any attention. What explains this oversight? In this article, I argue, first, that academics are held in the grips of an ideology that diverts attention away from the structural conditions of precarity, and second, that the gendered dimensions of such an ideology ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…Noonan (2015) argues that short-term academic contracts are no longer simply preparation for gaining a secure position but instead are increasingly substitutes for more secure posts. As Zheng (2018) notes, contingent academics are cheap, flexible and disposable, hence their appeal to universities in a hyper-competitive global market.…”
Section: Introductionmentioning
confidence: 99%
“…Noonan (2015) argues that short-term academic contracts are no longer simply preparation for gaining a secure position but instead are increasingly substitutes for more secure posts. As Zheng (2018) notes, contingent academics are cheap, flexible and disposable, hence their appeal to universities in a hyper-competitive global market.…”
Section: Introductionmentioning
confidence: 99%
“…Compliance, we contend, is a necessary condition of this social reproduction, a bodily reorientation toward a specificity of desire, demands, and regimens-coercion beyond typical labor. Connecting this to the academy, Zheng (2018) suggests that the shift in the ratio of tenure-track (TT) to non-tenure-track (NTT) faculty in the US, from 70% TT/30% NTT in 1969 to 30% TT/70% NTT in 2011 (Kezar and Maxey 2013), clarifies the precarity of academic labor and the gendered and racialized processes that inform a structure wherein women and people of color fill the majority ranks of NTT positions. Within the discipline of philosophy, the precarity is stark, as only half of PhDs find permanent employment, one-third of whom fill temporary positions (Jennings et al 2017).…”
Section: Ontological Labor In Academiamentioning
confidence: 99%
“…There used to be a substantial amount of social stigma attached to video and computer gaming, which was regarded as ‘e-heroin’ due to public concern over video game addiction in China (Lu, 2016; Yu, 2018). Previous studies have demonstrated that such under-represented groups affected by social stigma may be especially attached to meritocratic principles to validate and motivate themselves (Śliwa and Johansson 2014; Zheng, 2018). Therefore, although any athlete may show meritocratic characteristics, Chinese eSports practitioners and researchers particularly highlight the competitive rather than playful features of eSports and intentionally highlight the meritocratic characteristics of eSports as a way to overcome a negative reputation, to resist social stigmas, and to seek self-legitimization and self-value (Dai, 2019; Jonasson and Thiborg, 2010).…”
Section: Meritocratic Discoursementioning
confidence: 99%